Alzheimer‐associated Aβ oligomers impact the central nervous system to induce peripheral metabolic deregulation. Issue 2 (23rd January 2015) - Clarke, Julia R; Lyra e Silva, Natalia M; Figueiredo, Claudia P; Frozza, Rudimar L; Ledo, Jose H; Beckman, Danielle; Katashima, Carlos K; Razolli, Daniela; Carvalho, Bruno M; Frazão, Renata; Silveira, Marina A; Ribeiro, Felipe C; et al.
Abstract Alzheimer's disease (AD) is associated with peripheral metabolic disorders. Clinical/epidemiological data indicate increased risk of diabetes in AD patients. Here, we show that intracerebroventricular infusion of AD‐associated Aβ oligomers (AβOs) in mice triggered peripheral glucose intolerance, a phenomenon further verified in two transgenic mouse models of AD. Systemically injected AβOs failed to induce glucose intolerance, suggesting AβOs target brain regions involved in peripheral metabolic control. Accordingly, we show that AβOs affected hypothalamic neurons in culture, inducing eukaryotic translation initiation factor 2α phosphorylation (eIF2α‐P). AβOs further induced eIF2α‐P and activated pro‐inflammatory IKKβ/NF‐κB signaling in the hypothalamus of mice and macaques. AβOs failed to trigger peripheral glucose intolerance in tumor necrosis factor‐α (TNF‐α) receptor 1 knockout mice. Pharmacological inhibition of brain inflammation and endoplasmic reticulum stress prevented glucose intolerance in mice, indicating that AβOs act via a central route to affect peripheral glucose homeostasis. While the hypothalamus has been largely ignored in the AD field, our findings indicate that AβOs affect this brain region and reveal novel shared molecular mechanisms between hypothalamic dysfunction in metabolic disorders and AD.